Mechanical engineering : emerging vistas - Upadhyay, R.K.; Sinha, R.P.; Singh, Jagvir (New Delhi ; New Delhi : Narosa Publishing House, 2011)
"This established textbook is revised in line with the technical qualifications of new engineering apprenticeship standards at Level 3. Four new chapters cover static and dynamic engineering systems, fluid systems and additive manufacturing. It has worked examples, student activities, quizzes throughout the text, and end-of-unit questions"--
Includes bibliographical references and index.
Keywords: Mechanical engineering